The importance of state aid in rebuilding the sector potential using the example of EU maritime shipping - Skrzeszewska, Katarzyna; Waśniewska, Anetta (Znaczenie pomocy publicznej w odbudowaniu potencjału sektora na przykładzie unijnej żeglugi morskiej, 2019)
Maritime transport is an essential element of economic expansion. The fleet under the national flag enables the diversification of supply routes, and creates opportunities for the development of new areas of economic activity based on sea resources. Despite these obvious advantages the fleet registered under the EU flags is getting smaller. The aim of the article is: (1) an analysis of the importance of national fleets for the EU economy and reasons for the fleet reduction in the national registers, (2) assessment of the effects of the admissible state aid to maritime transport in the EU, (3) identification of factors positively affecting the potential of national fleets. The research was carried out using a critical analysis of literature and an econometric model with many variables explaining the phenomenon using the classical least squares method. The research results indicate that the use of protectionist policy tools does not bring the expected results, and the impact of market factors is more visibly reflected in the size of the fleets registered under the national flags than in the state aid
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 138-151